Changes in heterosis of maize (Zea mays L.) varietal cross hybrids after four cycles of reciprocal recurrent selection - Kolawole, A.O.; Menkir, A.; Blay, E.; Ofori, K.; Kling, J.G. (Springer, 2019)
Two improved tropical maize composites, TZL COMP3 and TZL COMP4; representing complementary heterotic pools have been subjected to four cycles of reciprocal recurrent selection (RRS) for two decades to enhance varietal cross performance. The objectives of this study were to evaluate the effect of selection on genetic gain in heterosis for grain yield and other agronomic traits of these composites. Ten parental populations representing the C0 to C4 of each composite and their crosses plus a varietal check were evaluated in a trial at eight environments in Nigeria. Grain yield of the varietal crosses increased with selection by 3.1% cycle–1. Mean grain yields of the C4 × C4 varietal cross exceeded that of a popular improved reference variety by 23%. Selection also reduced anthesis-silking interval, improved ear characteristics, phenotypic appeal and resistance to foliar diseases. Mid-parent heterosis (MPH) increased from 4% at C0 × C0 to 24% at C4 × C4. The average rate of genetic gain in heterosis for grain yield in population crosses was 3.1% possibly because of presence of non-additive gene effects. The results of our study present the potential usefulness of the advanced selection cycle as sources of diverse inbred lines with improved combining ability as well as improved varietal crosses that can be multiplied and deployed in areas with limited market access.